Clinical characteristics and perspectives of children and youths with type 1 diabetes attending Patan Hospital, Nepal (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Type 1 Diabetes Mellitus (DM1) has reportedly a high proportion of initial presentation as diabetic ketoacidosis, more in resource-poor settings. This study was designed to assess the demographics and clinical characteristics of DM1 patients as well as their perception of diabetes management in local scenario. Method: This is a cross-sectional study of data collected prospectively by a questionnaire survey among young patients with DM1 presenting to Medical and Paediatric Referral Clinics of Patan Hospital, Nepal during April 2016 to June 2016. Ethical approval was obtained. Demographics, and disease process- initial presentation of diabetic ketoacidosis, HBA1c target, and common problems were analyzed by SPSS using chi-square and Fisher exact tests, p